2010
DOI: 10.1371/journal.ppat.1001145
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the Hemagglutinin of the 2009 H1N1 Pandemic Virus: Potential for Strains with Altered Virulence Phenotype?

Abstract: A novel, swine-origin influenza H1N1 virus (H1N1pdm) caused the first pandemic of the 21st century. This pandemic, although efficient in transmission, is mild in virulence. This atypical mild pandemic season has raised concerns regarding the potential of this virus to acquire additional virulence markers either through further adaptation or possibly by immune pressure in the human host. Using the mouse model we generated, within a single round of infection with A/California/04/09/H1N1 (Ca/04), a virus lethal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
116
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(127 citation statements)
references
References 40 publications
9
116
2
Order By: Relevance
“…After this paper was submitted for publication, Ye et al reported that the insertion of mutations D131E and S186P into the pandemic strain A/California/04/ 09/(H1N1) increased the virus's pathogenicity in BALB/c mice (40). Indeed, our analysis detected these positions as discriminating between swine H1N1 and pH1N1 (Table 2), and D131 and S186 were identified as characteristic of the pandemic strain.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…After this paper was submitted for publication, Ye et al reported that the insertion of mutations D131E and S186P into the pandemic strain A/California/04/ 09/(H1N1) increased the virus's pathogenicity in BALB/c mice (40). Indeed, our analysis detected these positions as discriminating between swine H1N1 and pH1N1 (Table 2), and D131 and S186 were identified as characteristic of the pandemic strain.…”
Section: Discussionmentioning
confidence: 59%
“…Indeed, our analysis detected these positions as discriminating between swine H1N1 and pH1N1 (Table 2), and D131 and S186 were identified as characteristic of the pandemic strain. Interestingly, the amino acids we predicted to be swine H1N1 characteristics (131E and 186P) were shown to generate the pathogenic strain studied by Ye et al (40). An additional study published after the submission of this paper (41) disclosed two positions in the HA, namely, 200 and 227, as affecting receptor binding of the pandemic strain.…”
Section: Discussionmentioning
confidence: 85%
“…However, A(H1N1)pdm viruses circulating in Finland (2009-2010 and 2010-2011) with N125D and/or N156K were less sensitive to neutralization by sera from individuals that were vaccinated or infected with Cal/09-like viruses (70). D127E and S183P, identified following passage of Cal/09 through mouse lung, were also associated with reduced reactivity of ferret antisera raised to Cal/09 (71). In this study, we provide the first evidence, to our knowledge, that expression of glycans at site Asn 136 of A(H1N1) pdm viruses facilitates resistance to neutralizing Abs directed against Auck/09.…”
Section: Discussionmentioning
confidence: 97%
“…By serial passage of H1N1/09 virus in mice, Zhou et al found that the PB2-E158G mutation increased the morbidity and mortality of H1N1/09 in mice (11). Ye et al reported that five amino acid substitutions distributed in HA, PA, or NP protein from a mouse-adapted A/California/04/2009 (CA04) virus contributed to the lethal phenotype in mice (12). The role of the HA gene in the virulence of H1N1/09 viruses has also been recognized in other studies (13,14).…”
mentioning
confidence: 99%